Comparative outcome of cisplatin-capecitabine regimen with oxaliplatincapecitabine regimen in advanced gastric carcinoma: a quasi-experimental study: Comparative outcome of cisplatin-capecitabine regimen with oxaliplatin-capecitabine regimen in advanced gastric carcinoma (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Chemotherapy is the primary therapeutic choice for advanced gastric cancer. The goal of this study was to assess the effectiveness and toxicity of the cisplatin-capecitabine regimen versus the oxaliplatin-capecitabine regimen in treating advanced gastric cancer. Between February 2021 and March 2022, this quasi-experimental study was conducted on 64 advanced gastric cancer patients. Purposive sampling was used to include those who met the inclusion criteria and distributed them evenly between the two arms. Arm A got an injection of cisplatin (80 mg/m2 on day 1) with oral capecitabine (1000 mg/m2 b.i.d. on days 1–14), whereas arm B received an injection of oxaliplatin (130 mg/m2 on day 1) plus oral capecitabine (1000 mg/m2 b.i.d. on days 1–14), every 3 weeks for 6 cycles. A final check-up was done at 12 weeks after the treatment. In arm A, 18 (56.2%) patients exhibited partial response compared to 15 (46.9%) in arm B. Stable diseases were also reported in both arms (18.8% in arm A and 21.9% in arm B). There were 8 (25.0%) cases of progressive disease in arm A and 10 (31.2%) cases in Arm B. The median progression-free survival in arms A (5.6 months) was almost similar to arm B (5.9 months). The most prevalent toxicities in both arms were vomiting, diarrhea, anemia, neutropenia, oral mucositis, paresthesia, handfoot syndrome, and renal toxicity. There were no statistically significant variations in outcomes between the two arms. In conclusion, the cisplatincapecitabine regimen is as effective as the oxaliplatin-capecitabine regimen in advanced gastric cancer.BSMMU J 2022; 15(3): 180-185